Application of Arbuscula Mycorrhizal Fungi to Increasing N-total and P-available Soil for Eggplant (solanum melongena l.) Growth on Ultisol Soil - Ferdi Ferdi; Husna Husna; Namriah Namriah; Darwis DEA; Zulfikar Zulfikar; Resman Resman (Journal of Tropical Mycorrhiza, 2023)
Ultisol land is a physically and chemically poor piece of land because it needs special handling that must be done with extreme caution. Mikoriza Arbuskula fungi is one biological fertilizer technique to get around this issue. One of the tiny soil creatures that can coexist with the roots of land plants is the fungus Mikoriza Arbuskula. In order to support plant development and make it simpler for plants to absorb nutrients and maintain soil moisture, Mikoriza Arbuskula Fungi can symbiose with plant roots and form HIFA around young roots. The purpose of this study is: (1) to determine the effect of the application of the Mikoriza Fungi Arbuskula on increasing N-total and P-available on ultisol soil, (2) to determine the effect of the best Mikoriza Arbuskula Fungi application on the growth of eggplant in Ultisol. This research was conducted on experimental land II and the Laboratory of Ami Calay Sultra Faculty of Forestry University of Halu Oleo Kendari. The study was conducted in November - January 2023. This study used a group of randomized groups (shelves). Mushroom Mikoriza Arbuskula consists of 5 levels, namely M0 = without treatment, M1 = 5 g /polybag-1, M2 = 10 g / polybag-1, M3 = 15 g / polybag-1, M4 = 20 g / polybag-1. The results of the study show that the Mikoriza Arbuskula fungi affected the total increase in N and P-available ultisol soil, the results of the initial analysis of 0.03% increased to 0.13% and P available from 9.00 ppm increased to 17.50 ppm. Mikoriza arbuskula fungi with a dose of 20 g / polybag-1 provides better eggplant plant growth.